Leader Proteinase of the Beet Yellows Closterovirus: Mutation Analysis of the Function in Genome Amplification - Peng, Chih-Wen (American Society for Microbiology, 2000)
The beet yellows closterovirus leader proteinase (L-Pro) possesses a C-terminal proteinase domain and a nonproteolytic N-terminal domain. It was found that although L-Pro is not essential for basal-level replication, deletion of its N-terminal domain resulted in a 1,000-fold reduction in RNA accumulation. Mutagenic analysis of the N-terminal domain revealed its structural flexibility except for the 54-codon-long, 5′-terminal element in the corresponding open reading frame that is critical for efficient RNA amplification at both RNA and protein levels.